Bacteriological profile and antibiogram of blood culture isolates from bloodstream infections in a rural tertiary hospital in Nigeria - Oluwalana T. Oyekale; Bola O. Ojo; Adewale T. Olajide; Oluwatoyin I. Oyekale (AOSIS, 2022)
Background: Bloodstream infections (BSIs) are a cause of significant morbidity and mortality requiring urgent antibiotic treatment. However, there is widespread antibiotic-resistance from the bacterial causes, necessitating regular surveillance for drug-resistant bacteria and their antibiograms. Objective: This study isolated and identified various bacterial causes of BSIs, determined their antibiotic susceptibility patterns, and determined the best empirical treatment for cases of BSI in the setting. Methods: A cross-sectional study was carried out at the Federal Teaching Hospital, Ido-Ekiti, Nigeria between June 2020 and February 2021 on 177 blood culture samples from cases of BSI. Identification of isolated bacteria and antibiotic susceptibility testing of the isolates were carried out following the standard protocol. Results: Culture positivity in this study was 19.2%. No significant difference was seen in culture positivity between male and female participants (p = 0.97). Gram-negative enteric bacteria were predominantly isolated (67.6%), including Escherichia coli (29.4%) and Klebsiella aerogenes (20.6%). Staphylococcus aureus was the most common Gram-positive bacterium isolated (23.5%). Three (37.5%) S. aureus isolates were methicillin-resistant. All isolates were sensitive to meropenem, and 97.1% were sensitive to imipenem; other sensitivity patterns were: ceftazidime (85.3%), ciprofloxacin (79.4%), ofloxacin (79.4%), and gentamicin (76.5%). There was low sensitivity to ampicillin (32.4%) and cotrimoxazole (38.2%). All Gram-positive isolates, including methicillin-resistant S. aureus, were sensitive to vancomycin. Conclusion: Regular surveillance of isolate sensitivity patterns, formulation of hospital antibiotic policies based on existing data and compliance with treatment guidelines will promote rational antibiotic use and reduce resistance among bacteria.